(untitled) (Bangladesh Journal of Agricultural Research, 2014)
An experiment on the effect of different sources of Arbuscular mycorrhiza (AM) fungi on tomato seedlings (var. Roma VF) was conducted at the Bangladesh Agricultural Research Institute, Gazipur during rabi 2007-08 and 2008-09. Eight sources of AM fungi viz., AM-01 (Jessore), AM-02 (Rahmatpur), AM-03 (Joydebpur), AM-04 (Ullapara), AM-05 (Jamalpur), AM-06 (Hathazari), AM-07 (Ishurdi), and AM-08 (Rajshahi) were studied along with a control and mixed sources on tomato seedlings. Soil based AM inoculum at the rate of 2.0 kg/m2 was used. Biomass yield of tomato (Roma VF) increased from 14.8% to 53.6% in 2007-08 and 32.1% to 58.4% in 2008-09 over control by inoculation with different sources of AM. The highest biomass yield (301 mg/seedling) of tomato (Roma VF) was observed with AM-05 (Jamalpur source), which was higher to all AM sources except AM-07 (Ishurdi source). Nutrient uptake by tomato seedlings was improved by inoculation with AM fungi. The AM fungi from all the sources appeared to be effective in enhancing the growth and development of tomato seedlings. DOI: http://dx.doi.org/10.3329/bjar.v39i1.20067 Bangladesh J. Agril. Res. 39(1): 23-31, March 2014